When “Aging” meets “Intelligence”: smart health cognition and intentions of older adults in rural Western China - Li, Xiao-Yu; Li, Jun; Zhu, Ning-Li; Luo, Lei; Zhang, Si-Yu; Cheng, Wen-Wen; Li, Jia-Xue; Yu, Chen; Lu, Song-He; Zhu, Liang (Frontiers in Psychiatry, 2025)
BackgroundPopulation aging is occurring at an unprecedented pace, rendering “healthy aging” a critical issue of global importance. China is at the forefront of this demographic transformation and faces substantial challenges, especially in its western rural regions. In this context, smart health technology, propelled by advancements in medical care and information technology, emerges as a vital strategy to address the challenges associated with aging. Despite smart technologies’ promising potential, the cognitive and behavioral intentions of older adults living in underdeveloped areas remain poorly understood.MethodsThis study focuses on individuals aged 60 years and older residing in the rural regions of Western China. A total of 311 comprehensive datasets were collected using a questionnaire. These datasets encompass the fundamental cognitive understanding, usage requirements, and barriers faced by rural older adults regarding various aspects of their lives. The study aims to explore the attitudes, expectations, and personal perspectives of elderly rural residents towards smart health technology, as well as their views on its adoption. Finally, drawing on the literature, we constructed a structural equation model to analyze the primary factors influencing the cognitive and behavioral intentions of rural older adults toward smart health.ResultsThe survey results indicate significant progress in promoting smart health initiatives within the rural areas of western China. While the older adult population demonstrates a basic understanding of smart health, particularly concerning wearable devices such as blood pressure monitors and oximeters, this understanding also underscores the urgent need for improved health management and enhanced quality of life among rural older adults. As their comprehension of smart health deepens, a majority of older respondents recognize its potential to benefit personal health management, fulfill their daily needs, and highlight its importance for rural development. In terms of cognitive pathways toward adopting smart health, older individuals prefer recommendations from their children or spouses, as well as guidance from healthcare professionals such as doctors or nurses. Overall, older residents in rural western China exhibited a strong willingness to embrace smart health practices. After experiencing smart health technology, they were inclined to adopt it as their primary method of health management and recommend it to others, thereby presenting promising prospects for future smart health promotion in underdeveloped regions.ConclusionSmart health has immense potential to enhance the quality of life of older adults, driven by a genuine and pressing demand expressed by rural older adults and a strong behavioral intention toward adoption. Despite facing challenges, such as limited cognitive diversity in smart health, economic constraints, technical usability barriers, and lack of social and familial support, future initiatives must prioritize the actual needs of older adults in rural areas. This requires effective communication strategies and service models tailored to the specific conditions of underdeveloped regions in order to expand and deepen the use of smart health applications. Moreover, concerted efforts by governments, enterprises, and all sectors of society are essential to deliver more accessible and cost-effective health management and services to older adults. Ultimately, these efforts will contribute to enhancing the overall well-being and quality of life of older adults.